Upaya Meningkatkan Kreativitas Biologi Siswa Melalui Penerapan Model Problem Based Learning (PBL) Di SMA Negeri 1 Sipirok - Hoirunnisa Nasution; Melvariani Syari Batubara; Muhammad Darwis (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This research aims to improve creativity, student activity and management of biological learning through the application of learning model of Problem Based Learning (PBL) in class XI IPA-4 SMA Negeri 1 Sipirok T. P 2018/2019. This type of research is class action research (PTK) using two learning cycles. Each cycle starts with planning, implementation, observation, and reflection. The data collection techniques used are tests and observations with data collection tools in the form of test sheets and observation sheets. Based on the results of the study, obtained the test result on the cycle I with an average value of 71.84 students who completed 9 people (71.97%) And in cycle II was obtained an average value of 93.59 students over 30 people (93.75%) So from cycle I to cycle II occurred an increase of 7 people (21.88%). The results of the observation on student learning activities in cycle I were obtained an average value of 2.32 (58.28%), Cycle II 3.05 (76.56%) An increase of 18.28% of the criteria is quite good criteria. The management of biological learning from cycle I gained an average percentage of 70% and Sikulus II to 91%. Thus, from cycle I to cycle II There has been an increase of 21% of the circulation enough to be a good criterion. This study was terminated in cycle II because success indicators have been achieved and meet the criteria of submission so that through the model learning Problem-Based Learning (PBL), it can be increased Creativity, activity and management of biological learning of studentsKeywords: Learning creativity, learning activity, Problem Based Learning